Dental Characteristics of Different Types of Cleft and Non-cleft Individuals - Alam, Mohammad Khursheed; Alfawzan, Ahmed Ali (Frontiers in Cell and Developmental Biology, 2020)
Objective: The objective of this study was to compare the novel artificial intelligence-driven lateral cephalometric (Late. Ceph.) analysis of 14 different dental characteristics (DC) among different type of cleft lip and palate (CLP) and non-cleft (NC) individual. Materials and Methods: A retrospective study was conducted on 123 individuals (31=NC, 29=BCLP [Bilateral cleft lip and palate], 41=UCLP [Unilateral cleft lip and palate], 9=UCLA [Unilateral cleft lip and alveolus], and 13=UCL [Unilateral cleft lip]) with an average age of 14.77 years. Demographic details gathered from the clinical records. A novel artificial-intelligence driven Webceph software has been used for the Late. Ceph. analysis. A total of 14 different types of angular and linear DC measurements were analyzed and compared among groups. Two-way ANOVA and multiple comparison statistics tests were applied to see the differences between gender and among different type of CLP versus NC subjects. Results: Of the 14 DC tested, no significant gender disparities were found (p > 0.05). In relation to different type of CLP versus NC subjects, 8 over 14 DC were statistically significant (p < 001 to p = 0.03). Six other DC variables show insignificant (p > 0.05) noteworthy alterations in relation to type of CLP. Conclusion: Based on the results, type of CLP revealed significantly altered DC compared to NC. Among different type of CLP, BCLP exhibit maximum alteration in different DC.